Reviewed book: Dalia STREIMIKIENE (Ed.) (2025), Societal Challenges and Opportunities of Low-Carbon Energy Transformations, CRC Press, 400 p. - Simanavicius, Arturas (Transformations In Business & Economics, 2025)
Authors: Dalia STREIMIKIENE (Ed.) Authors’ Affiliation: Kaunas faculty Vilnius University, Lithuania Title: SOCIETAL CHALLENGES AND OPPORTUNITIES OF LOW-CARBON ENERGY TRANSFORMATIONS Subtitle: Monograph Year: 2025 Publisher: CRC Press Volume: 400 pages Type of publication: e-book Language: English ISBN: 9781003517481 For more information contact: dalia.streimikiene@khf.vu.lt
Keywords: none